A principle of economy in derivation in L2 grammar: Do everything in narrow syntax. (October 2021) - Wakabayashi, Shigenori
This article proposes a novel account for the overuse of free morphemes and underuse of bound morphemes in English as a second language (L2) based on the framework of Distributed Morphology. It will be argued that an Economy Principle 'Do everything in Narrow Syntax (DENS)' operates in the L2 learner's computational system. Consequently, derivation in Morphology becomes as limited as possible except when applying Vocabulary Items to syntactic objects (Vocabulary Insertion). This results in non-target-like use/acceptance of certain morphemes: Bound morphemes are often omitted in early L2 grammar, and alternative free morphemes may apparently be used instead. Two types of data, namely the overuse of be reported in previous research, and the preference of to- infinitives over -ing gerunds in early L2 grammar, will be presented in support of the proposal, and the plausibility of the operation of DENS will be discussed.